Molecular Inferences on Scomberomorus brasiliensis, From the Western South Atlantic, Based on Two Mitochondrial Genes - da Cunha, Divino B.; Rodrigues-Filho, Luis Fernando S.; de Luna Sales, João Braúllio; Rêgo, Pericles; Queiroz, Cleonilde; Sampaio, Iracilda; Vallinoto, Marcelo (Frontiers in Marine Science, 2020)
The Serra Spanish Mackerel, Scomberomorus brasiliensis is one of the principal fishery resources found in the tropical and subtropical waters of the western South Atlantic. Declining catches of S. brasiliensis off the coast of northeastern Brazil indicate that this species is being overfished. Despite the importance of this species to local fisheries, few data are available on its genetic diversity or population parameters. Given this scenario, the present study evaluated the genetic variability of S. brasiliensis off the coast of the western South Atlantic, based on mitochondrial genes. We compiled two databases, one with partial sequences of the MT-CYB gene (N =105), and the other of the MT-ND4 gene of the Serra Spanish Mackerel, sampled from eight localities, ranging from Cumana in Venezuela to Paranaguá, in soutern Brazil. The results of the analysis indicate low levels of genetic diversity in the study. Samples from Cumana, on the coast of Venezuela were the most differentiated, although the results of the AMOVA were not significant. The PhiST values, the genetic divergence, and the haplotype network all indicate the widespread sharing of haplotypes by the mackerel from all the different localities. Analyses of the historical demography, based on both markers, indicate the occurrence of past population expansion, coinciding with fluctuations in sea level that occurred 10,000 years ago. The demographic and phylogeographic analyses of the mitochondrial DNA revealed the existence of a single genetic stock of S. brasiliensis on the coast of the western South Atlantic according to. These findings are fundamental to the development of effective conservation strategies.